STRATEGI KOPING ORANG TUA TERHADAP ANAK AUTIS DAN POLA ASUH ORANG TUA - Ma’rifah, Asirotul; Suryantini, Naning Puji Suryantini; Mardiyana, Rina (Unusa Press, 2018)
Autism is still a nightmare for most parents. Parents with autism can be very stressful when dealing with a hyperactive child's behavior, aggressive and passive. Stress experienced by parents of children with autism will affect the ability of parents in the parenting role, especially in relation to coping strategies have in dealing with problems of children. The participation of parents is crucial the success of socializing with children with autism in the general population. This study aims to determine the relationship of coping strategies parents of autistic children and parenting parents. This type of research is an analytic correlation with cross sectional approach. The population in this study were all parents of autistic children in SLB Muhammadiyah Mojokerto numbering 15 people. Samples in this study were all parents of autistic children in SLB Muhammadiyah Mojokerto which totaled 15 people by using total sampling technique. Collecting data using questionnaires. Data analized use cross tabulation, presented in a frequency distribution. On cross-tabulation obtained results tend to use maladaptive coping strategies permissive parenting that is 8 (53.3%), there are also respondents who use adaptive coping strategies using authoritarian parenting as much as one person (16.7%), and adaptive coping strategies tend using democratic parenting style as much as 5 people (33.3%). Expected parents still seeking information to broaden their parents on coping strategies of parents of autistic children and parenting parents as well as parents to give special attention for children with autism to the development and advancement of their lives because they have the same rights as any other normal child.